2016
DOI: 10.1093/gbe/evw225
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the MRSA Isolate HC1335 from ST239 Lineage Displaying a Truncated AgrC Histidine Kinase Receptor

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is still one of the most important hospital pathogen globally. The multiresistant isolates of the ST239-SCCmecIII lineage are spread over large geographic regions, colonizing and infecting hospital patients in virtually all continents. The balance between fitness (adaptability) and virulence potential is likely to represent an important issue in the clonal shift dynamics leading the success of some specific MRSA clones over another. The accessory gene regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(57 reference statements)
0
6
1
Order By: Relevance
“…aureus strain T0131 and S. aureus strain HC1335) were found to contain a transposase gene between the hypothetical gene adjacent to agrD and agrC (Supplementary Figure S1). A previous study from Botelho et al,identified IS256 transposase in these two strains and suggested that this transposase truncated agrC into two, which inhibited the gene and subsequently the regulation of agr locus [Botelho et al, 2016]. While we were unable to identify any conserved motifs in the hypothetical gene between agrD and agrC to define it as a histidine kinase, we did observe five transmembrane helices.…”
Section: Orientation Of Agr Genes Classifies S Aureus Strains Into Fcontrasting
confidence: 58%
See 1 more Smart Citation
“…aureus strain T0131 and S. aureus strain HC1335) were found to contain a transposase gene between the hypothetical gene adjacent to agrD and agrC (Supplementary Figure S1). A previous study from Botelho et al,identified IS256 transposase in these two strains and suggested that this transposase truncated agrC into two, which inhibited the gene and subsequently the regulation of agr locus [Botelho et al, 2016]. While we were unable to identify any conserved motifs in the hypothetical gene between agrD and agrC to define it as a histidine kinase, we did observe five transmembrane helices.…”
Section: Orientation Of Agr Genes Classifies S Aureus Strains Into Fcontrasting
confidence: 58%
“…However, we also identified some strains of type I and type II which may have incorporated a "selfdestruct" mechanism of the agr inactivation by incorporating transposase or additional hypothetical genes in the agr locus. Inactivation of agr appears to confer a fitness advantage under the conditions of antibiotic selection, in vivo environment, and biofilm formation (Botelho et al, 2016;Paulander et al, 2012;Tan et al, 2015). Loss of agr function has been associated with resistance to host cationic antimicrobial peptides, tolerance to vancomycin, and development of intermediate resistance to vancomycin, a phenotype that is associated with treatment failure in bloodstream infections (Fischer et al, 2011;Mwangi et al, 2007;Sakoulas et al, 2002Sakoulas et al, , 2005Tsuji et al, 2007;Vandamme et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…7 A ). Strain 38884 contains an IS256 transposase gene which disrupts the agrC gene resulting in truncated nonfunctional AgrC as previously reported in S. aureus T031 and HC1335 ( 96 , 97 ). CC398 strain 38888 is IEC positive carrying the prophage ΦSa3 which disrupts the hlb gene.…”
Section: Resultsmentioning
confidence: 88%
“…Two of the type I strains ( S. aureus strain T0131 and S. aureus strain HC1335) were found to contain a transposase gene between the hypothetical gene adjacent to agrD and agrC (Supplementary Figure 1 ). A previous study from Botelho et al (2016) identified IS256 transposase in these two strains and suggested that this transposase truncated agrC into two, which inhibited the gene and subsequently the regulation of agr locus. While we were unable to identify any conserved motifs in the hypothetical gene between agrD and agrC to define it as a histidine kinase, we did observe five transmembrane helices.…”
Section: Resultsmentioning
confidence: 91%
“…However, we also identified some strains of type I and type II which may have incorporated a “self-destruct” mechanism of the agr inactivation by incorporating transposase or additional hypothetical genes in the agr locus. Inactivation of agr appears to confer a fitness advantage under the conditions of antibiotic selection, in vivo environment, and biofilm formation ( Paulander et al, 2012 ; Tan et al, 2015 ; Botelho et al, 2016 ). Loss of agr function has been associated with resistance to host cationic antimicrobial peptides, tolerance to vancomycin, and development of intermediate resistance to vancomycin, a phenotype that is associated with treatment failure in bloodstream infections ( Sakoulas et al, 2002 , 2003 , 2005 ; Mwangi et al, 2007 ; Tsuji et al, 2007 ; Fischer et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%